Association between visceral adiposity index and osteoarthritis in U.S. adults aged 50 and older: a cross-sectional study - Zitian Wang; Guang Peng; Yuquan Jiang; Jintao Qu; Fengfu Wu (Frontiers in Nutrition)
BackgroundExisting evidence linking visceral adiposity index (VAI) to osteoarthritis (OA) remains limited and requires further investigation. This study aimed to evaluate the potential relationship between higher VAI scores and an increased risk of OA.MethodsA retrospective cross-sectional analysis was conducted using data from 9,464 participants aged 50 and older, sourced from the 2011 to 2018 National Health and Nutrition Examination Survey (NHANES). The VAI was categorized into three tertiles, with the first tertile (T1) representing the lowest VAI and third tertile (T3) the highest. Weighted logistic regression was employed to examine the association between VAI and OA. To explore potential non-linear relationships, smoothed curve fitting and threshold effect analyses were performed. Subgroup analyses were performed to validate these findings.ResultsThe average age of the study population was 63.16 ± 9.05 years, and 47.22% were male. After adjusting for confounding factors, a statistically significant positive correlation was observed between VAI and OA risk (OR = 1.03, 95% CI: 1.01–1.06, P < 0.01). Participants in the highest VAI tertile exhibited a 35% greater likelihood of developing OA compared to those in the lowest tertile (OR = 1.35, 95% CI: 1.06–1.70, P = 0.015). Furthermore, multivariate restricted cubic spline (RCS) regression analysis revealed a non-linear relationship (non-linear P < 0.05) with a threshold effect at a VAI value of 3.9. Subgroup analyses showed no significant interaction effects (all P-values for interaction > 0.05).ConclusionThis study highlights a significant association between elevated VAI and an increased risk of developing OA in individuals aged 50 and older. These results emphasize the potential of the VAI as a risk factor for OA and warrant further research to explore its role in prevention and management strategies in older populations.